Penerapan Kelengkapan Keselamatan dan Kesehatan Kerja (K3) Pada UMKM Konstruksi Logam - Anak Agung Alit Triadi; Nur Kaliwantoro; I Gede Bawa Susana; Maharsa Pradityatama; Akbar Tawaqqal; Lalu Marvin Apriyadi; Muhammad Alkaff (Jurusan Teknik Mesin FT Universitas Mataram, 2026)
Occupational Safety and Health (OSH) implementation in small and medium metal construction enterprises is often neglected, particularly regarding non-ergonomic working postures and the low use of personal protective equipment (PPE). These conditions increase the risk of work-related fatigue, occupational diseases, and workplace accidents. This community service program aimed to improve workersâ€™ knowledge and behavior toward healthy work concepts and PPE utilization in a metal construction MSME through counseling and hands-on demonstrations. The activity was carried out in one day at the partnerâ€™s workshop, involving all workers and the business owner. The program adopted a counseling and implementation-oriented training design, using a five-item pre-test and post-test questionnaire on healthy work concepts, OSH, and PPE use. The results indicate a substantial improvement in OSH knowledge and behavior. The average percentage of â€œyesâ€ responses increased from approximately 16% at pre-test to about 92% at post-test; PPE use rose from 40% to 100%, and workers who reported always using PPE increased from 20% to 80%. The partner also began to understand and apply basic ergonomic principles in working posture and workstation arrangement. It can be concluded that the dissemination and demonstration of healthy work concepts and PPE use effectively enhanced OSH awareness and behavior among workers in the metal construction MSME, thus supporting business continuity through a safer, more comfortable, and more productive work environment.